P Pengaruh Pengetahuan Keamanan Pangan Terhadap Penanganan Higiene Sanitasi di Grand Hyatt Bali: Pengaruh Pengetahuan Keamanan Pangan Terhadap Penanganan Higiene Sanitasi di Grand Hyatt Bali - Fajri, Natasya Nuraini; Sabudi , I Nyoman Sukana; Kalpikawati, Ida Ayu (JURNAL GASTRONOMI INDONESIA, 2024)
The study aimed to determine the influence of food safety knowledge on handling food hygiene and sanitation at the Grand Hyatt Bali Hotel. The sample comprised 80 respondents, namely food and beverage product employees, food and beverage service, and stewards, using the purposive sampling method of distributing questionnaires. The data analysis technique uses Simple Linear Regression, Coefficient of Determination, and t-test using SPSS version 25 for Windows. The results of data analysis show that food safety knowledge partially has a positive and significant effect on handling food sanitation hygiene, where the t value is 10,948> 1,991, and the sig value is 0.000 <0.050. The magnitude of the influence of food safety knowledge on the handling of food sanitation hygiene is 60,6%. The conclusion is that food safety knowledge has a positive and significant impact on handling food sanitation. The advice given is that Grand Hyatt Bali is expected to increase the intensity of providing information about the risk of contamination, checking uniform dress, checking the quality of food processing tools and equipment, and appealing to employees who are handling food when they are suffering from diseases that can affect food safety.